Guidelines for process safety during the transient operating mode : managing risks during process start-ups and shut-downs (American Institute of Chemical Engineers ; John Wiley & Sons, Inc., 2021)
"Process industries bring vast benefits to our daily lives, but we do not live in a risk-free environment and mistakes are made. The timing for the highest risk period for most facilities occurs during start-up and shutdowns - also known as "transient" operations. Since transient operations, in general, for continuous chemical processes are performed less frequently, they have increased operational risks. This increased risk is due, in part, to an increased likelihood for procedural errors and the special hazards associated with the start-up or shutdown, especially since the process is not running under normal, steady state conditions. In addition, it may not be possible to address the many temporary and potentially hazardous conditions which could occur during the start-up or shutdown of these complex processes"--